Fish farming for diversifying cocoa production in Côte d’Ivoire: Typology of practices - Antoine K. Kouadio; Elodie Pepey; Lucas Fertin; Henri-Joel K. Niamien; Seri Brou; Charles K. Boussou; Simon Pouil (Aquaculture Reports)
Fish farming in Côte d’Ivoire has been promoted as a diversification strategy for cocoa producers, yet the sector exhibits significant heterogeneity in farming practices, which remains poorly documented. This study aimed to classify fish farming systems and identify key determinants of their performance. Surveys were conducted with 45 farmers across three cocoa-producing regions - Bédiala, Méagui, and Sinfra - and data were analyzed using Factor Analysis of Mixed Data (FAMD) and clustering analysis, leading to the identification of three distinct farm types. Type 1 farms, found in Bédiala, have the largest production areas (median: 2.9 ha) and predominantly practice polyculture of Nile tilapia (Oreochromis niloticus), bony tongue (Heterotis niloticus), and catfish (Clarias spp.), often integrated with rice farming. Type 2 farms, found in Sinfra, employ the most intensive practices, characterized by the use of monosex tilapia fingerlings and reproductive control via banded jewelfish (Hemichromis fasciatus), resulting in the highest yields (median: 1033 kg ha⁻¹ yr⁻¹). Type 3 farms, found in Méagui and Sinfra, are the least productive (median: 450 kg ha⁻¹ yr⁻¹), constrained by longer production cycles and limited technological adoption. These findings reveal significant regional disparities in fish farming practices and productivity, underscoring the need for tailored policy interventions. Strategies should focus on promoting improved production techniques in low-yielding systems while supporting sustainable intensification in more advanced farms to enhance the sector’s contribution to rural livelihoods and food security.